Obesity may not be related to pathologic response in locally advanced rectal cancer following neoadjuvant chemoradiotherapy - Bao, Quoc Riccardo; Crimì, Filippo; Valotto, Giovanni; Chiminazzo, Valentina; Bergamo, Francesca; Prete, Alessandra Anna; Galuppo, Sara; El Khouzai, Badr; Quaia, Emilio; Pucciarelli, Salvatore; Urso, Emanuele Damiano Luca (Frontiers in Oncology, 2022)
Background. The aim of this study is to evaluate the correlation of BMI and body fat composition (measured with radiological fat parameters (RFP)), and pathological response after neoadjuvant chemoradiotherapy for locally advanced rectal cancer patients. The secondary aim of the study was to assess the role of BMI and RFP on major surgical complications, overall survival (OS) and disease-free survival (DFS). Methods. All patients who underwent surgical resection following nCRT between 2005 and 2017 for mid-low rectal cancer were retrospectively collected. Visceral (VFA), superficial fat area (SFA), visceral/superficial fat area ratio (V/S), perinephric fat thickness (PNF) and waist circumference (WC) were estimated by baseline CT scan. Predictors of pathologic response and post-operative complications were investigated using a logistic regression analysis. The correlations between BMI and radiologic fat parameters, and survival were investigated using the Kaplan-Meier method and log-rank test. Results. Out of 144 patients included, and a complete (TRG1) and major (TRG1+2) pathologic response was reported in 32(22%) and 60(45.5%) cases, respectively. A statistically significant correlation between BMI and all the RFP was found. At a median follow-up of 60 (35-103) months, no differences in term of OS and DFS were found considering BMI and radiologic fat parameters. At univariable analysis nor BMI, nor radiologic fat parameters were predictors of complete or major pathologic response; nevertheless VFA, V/S>1, and BMI were predictors of post-operative major complications. Conclusions. We found no associations between BMI and body fat composition, and pathological response to nCRT, although VFA, V/S and BMI were predictors of major complications. BMI and RFP are not related to worse to long term OS and DFS.